Analisis Program Restrukturisasi Perbankan pada Masa Pandemi Covid-19 di Indonesia (Tahun 2019 - 2023) - Dedy Sunaryo Nainggolan (AKUNTANSI 45, 2025)
The COVID 19 pandemic has tested the resilience of financial systems worldwide, including in Indonesia, by creating sudden and unpredictable economic disruptions that required swift policy responses from governments and regulators. These conditions challenged banking institutions to formulate appropriate strategies not only to survive but also to sustain growth amid rising economic pressure. One major policy introduced as part of the national economic recovery was a credit restructuring program, implemented to mitigate the risk of increasing problem loans and to stabilize the banking sector. This study aims to analyze the implementation of banking credit restructuring programs during the COVID 19 pandemic and to assess whether these measures were effective solutions or merely short term preventive actions. The analysis employs the CAMEL method using banking statistical data from January 2019 to December 2023. The findings show that credit restructuring helped maintain strong capital adequacy ratios and supported operational efficiency. Moreover, banks were generally able to generate stable profits during the pandemic, contributing to sustainable capital and operational strength. However, the analysis of non performing loans indicates the need for closer monitoring of banks with NPL levels exceeding 2 percent. Long term effectiveness depends on robust early warning systems and the integration of restructuring policies within a comprehensive macroprudential framework.